English education in EFL context: Integrated approach for collaborative writing in the university level - Amrih Bekti Utami (LPPM UNY, 2014)
This research was aimed at finding out the implementation of the integrated approach of writing in English for Foreign Language (EFL) context. The approach was set by adjusting three different approaches namely, product, process, and genre approach. There were 20 sophomores students of a private university in Indonesia who became the participants of this study. By implementing classroom action research, the study was carried out during the first half second semester. It consisted of two cycles and each cycle covered four steps: plan, observe, act, and reflect. The data were obtained from the observation during the implementation of the actions as the qualitative data and the students’ writing scores of the pre-test and post-test as the quantitative data. The result of this study showed that the use of integrated approach for collaborative writing was effective to improve students’ writing skills. Research results it showed that the students were able to create positive relationship when they worked collaboratively in groups. They were also offered the opportunity to give and receive immediate feedback on language used on their writings. Thus, the teaching-learning process became more interesting and the students enjoyed the writing process. The improvement was also found in the writing aspects namely, content, organization, vocabulary, language use, and mechanics. As a result, the students could perform better writing on their texts.